Komunitas Fitoplankton dan Konsentrasi Nutrien di Waduk Jatigede - Randi FItriadi; Niken Tunjung Murti Pratiwi; Rahmat Kurnia (Jurnal Ilmu Pertanian Indonesia, 2021)
Jatigede reservoir is a new reservoir in West Java Province. There is not much information about phytoplankton and nutrients in this reservoir. The aim of the research was to study the relationship between phytoplankton community and nutrient in the reservoir. The research was conducted during the dry season, from September to October 2018. Analyzed parameters were phytoplankton abundance, diversity and dominance index, orthophosphate, nitrite, nitrate, and ammonium. Reservoir zonation was divided by cluster analysis. The relationship between phytoplankton and nutrients was analyzed by principal component analysis and Pearson’s correlation test. Phytoplankton in Jatigede Reservoir consisted of Bacillariophyceae, Chlorophyceae, Cyanophycea, Dinophyceae, and Euglenophyceae within 20333‒25308 cell/L. Nitrate concentration ranged within 0.6684‒3.6115 mg/L. Nitrite concentration ranged between 0.0544‒0.2301 mg/L and ammonium ranged within 0.00538‒0.2460 mg/L. The strongest correlation between phytoplankton and nutrients were shown by Cyanophyceae and Dinophyceae, especially with the concentration of orthophosphate, nitrate, nitrite, and ammonium (r > 0,78). Keywords: Cyanophyceae, orthophosphate, nitrate, nitrite